Uji toksisitas ekstrak daun tembakau (Nicotiana tabacum L.) terhadap mortalitas ulat Spodoptera frugiperda J.E. Smith pada tanaman jagung - Syahrani, Kristinda; Purnomo, Purnomo; Sudarsono, Hamim; Swibawa, I Gede (Universitas Lampung, 2025)
Corn (Zea mays L.) is an annual cereal crop that has high economic value and has the potential to be developed in Indonesia. However, corn production can be hindered due to the attack of caterpillar pests (Spodoptera frugiperda J.E Smith). The fall armyworm attacks the young leaves of corn plants which can cause the failure of leaf shoot formation. However, the attack can be controlled by using plant-based pesticides. One of the plants that can be used as a plant-based pesticide is tobacco leaves (Nicotiana tabacum L.). This study aims to determine the effect of several consentration of tobacco leaf extract on the mortality of fall armyworm in vitro as well as to determine LC50 from all S. frugiperda test larvae that have been treated with tobacco leaf extract. This research was carried out in January-June 2024 at the Plant Pest Science and Biotechnology Laboratory, Department of Plant Protection, Faculty of Agriculture, Lampung University. This study uses Randomized Group Design (RAK) for the basis of grouping with 6 treatments and 4 replications. Tobacco leaf extract used in this study were: 0% (control), 0,5% (T1), 1% (T2), 1,5% (T3), 2% (T4), 2,5% (T5) with 4 replications so that 24 experimental units were obtained, each experimental unit was in the form of 10 instar larvae of 3 corn caterpillars. The results of this study showed that the use of tobacco leaf extract at concentrations of 1,5%, 2%, and 2,5% caused mortality of 100% for 30 days of observation.